OCCLUSAL VENEERS AND DSD NATURAL RESTORATION FOR THE REHABILITATIONOF BIOCORROSION - Wuislane Lúcia Ribeiro Souza; Ângelo Raphael Toste Coelho Segundo; Tayane Holz Resende; Terumitsu Sekito Júnior (Portal de Periódicos da Marinha do Brasil, 2020)
Modern life increased the incidence of biocorrosion, demanding aesthetic and minimally invasive approach for the rehabilitation of these patients. At the same time, the improvementof adhesive dentistry, restorative materials and Computer Aided Design and Computer Aided Manufacturing (CAD/CAM) systems allowed the improvement on aesthetic with minimized time using effective digital approaches. This manuscript presents an approach with ultra-thin occlusal veneers to augmentation of vertical dimension and sandwich approach (semi-direct composite on palatal and ceramic on labial) to restore biocorrosion. The full mouth CAD-CAM rehabilitation involved posterior occlusal veneers using the software ́s anatomic database (biogeneric individual) and natural anterior algorithms obtained by integration between Digital Smile Design (DSD) and CAD-CAM (DSD - Natural Restoration). Therefore, the chairside mode is effective and less time consuming, associated to DSD-Natural Restoration improved anterior esthetic for labial ceramic veneers.